2019
DOI: 10.1021/acs.jafc.9b06531
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics Provides Novel Insights into Understanding the Bee Pollen Lipids Transepithelial Transport and Metabolism in Human Intestinal Cells

Abstract: Bee pollen (BP) shows profound gut-protecting potentials. BP lipids (BPLs) mainly composed by phospholipids and polyunsaturated fatty acids might be one of the important contributors, while how BPL exerts gut-protecting effects and is transported through intestinal cell monolayers need to be investigated. Here, we exploited a strategy that combines an UPLC-Q-exactive orbitrap/MS-based lipidomics approach with a human intestinal cell (Caco-2) monolayer transport model, to determine the transepithelial transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Similarly, glycerophospholipid and sphingolipid metabolism regulation was explored in dextran sulfate sodium (DSS)-induced intestinal barrier dysfunction Caco-2 cells. 15 Sun et al suggested that the antioxidative mechanism of geissoschizine methyl ether in glutamate-induced HT-22 cells is mediated via lipid metabolism regulation. 16 However, few studies have focused on the photoprotective effects of FX in RMCs, and the protective mechanism of FX against UVB irradiation in the retina is not well-understood.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, glycerophospholipid and sphingolipid metabolism regulation was explored in dextran sulfate sodium (DSS)-induced intestinal barrier dysfunction Caco-2 cells. 15 Sun et al suggested that the antioxidative mechanism of geissoschizine methyl ether in glutamate-induced HT-22 cells is mediated via lipid metabolism regulation. 16 However, few studies have focused on the photoprotective effects of FX in RMCs, and the protective mechanism of FX against UVB irradiation in the retina is not well-understood.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Vats et al found that ferroptosis induced by intracellular cellular inflammation due to UVB is related to excessive phospholipid peroxidation. Similarly, glycerophospholipid and sphingolipid metabolism regulation was explored in dextran sulfate sodium (DSS)-induced intestinal barrier dysfunction Caco-2 cells . Sun et al suggested that the antioxidative mechanism of geissoschizine methyl ether in glutamate-induced HT-22 cells is mediated via lipid metabolism regulation …”
Section: Introductionmentioning
confidence: 99%
“…To address this problem, more powerful techniques are required, and mass spectrometry (MS) exerts overwhelming potentials in lipid structure elucidation. In recent years, high-resolution MS, such as quadrupole time-of-flight MS (Q-TOF-MS) and Orbitrap, has been developed and applied in untargeted lipid analysis of different food matrices including fish, meat, and milk. When combined with highly selective ultraperformance liquid chromatography (UPLC), this advanced analytical technique enables the identification of hundreds of lipids in an unbiased way and has demonstrated its feasibility and potential in food science research at the molecular level. In terms of egg yolk lipids, previous studies using MS-based lipidomics approaches were mainly focused on a certain class or several lipid classes from common or various types of eggs. For example, Ali and co-workers identified 57 PL molecules in duck, hen, and quail egg yolk samples . To the best of our knowledge, there are limited studies that systematically investigate the lipidome changes in eggs after dietary manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…The JM25-1 alone has no significant impact on ZO-1, which is shown in Figure S1 . Additionally, transepithelial electrical resistance (TEER) of Caco2 cell monolayers is a common model used to investigate the permeability of the intestinal barrier [ 23 ]. The TEER value continuously dropped due to the co-culture with the medium of HMC-1 cells pre-treated with CRH.…”
Section: Resultsmentioning
confidence: 99%